2019
DOI: 10.1007/s41885-019-0039-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits by and Hospitalizations of Senior Diabetics in the Three Years Following Hurricanes Katrina and Rita

Abstract: While prior studies have investigated health care utilization immediately following disasters, few have examined utilization beyond that period. We use individual-level U.S. Medicare claims data for three years prior to (2002-2004) and after (2006-2008) Hurricanes Katrina and Rita to investigate whether senior diabetics affected by the storms had a greater number of emergency department visits and days hospitalized in the three years following the storms. An event study was conducted using regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…2 Elevations in postdisaster geriatric emergency department visits 15 and cardiac events 16 were seen after Hurricane Sandy, and also in a combined study looking at Hurricanes Rita and Katrina. 3,17 This study also found significant increases in all-cause hospital admissions when examining eight separate, large-scale hurricanes. Prior research has described surges in hospitalization after hurricanes, however most of these reports have been limited to one disaster 18 or the immediate period after a disaster.…”
Section: Discussionsupporting
confidence: 52%
“…2 Elevations in postdisaster geriatric emergency department visits 15 and cardiac events 16 were seen after Hurricane Sandy, and also in a combined study looking at Hurricanes Rita and Katrina. 3,17 This study also found significant increases in all-cause hospital admissions when examining eight separate, large-scale hurricanes. Prior research has described surges in hospitalization after hurricanes, however most of these reports have been limited to one disaster 18 or the immediate period after a disaster.…”
Section: Discussionsupporting
confidence: 52%
“…Our strategy intentionally over-sampled (up to 50%) those with Black and/or African American racial, biracial or multiracial identities as a novel strategy to combat racial data bias and develop a survey based on the population with the greatest demonstrated disparity for disaster-related assessment outcomes at the household level. (3, 4) Cognitive interviewing is generally conducted with 10 participants(2). We intentionally doubled this sample size in order to include a full cognitive interviewing sample size panel of those with Black and/or African American racial identities.…”
Section: Qualitative Approach and Research Paradigmmentioning
confidence: 99%
“…Rising global surface temperatures increase the risk for and severity of droughts, floods, storms and other forms of severe weather and natural hazards (2). In the United States, weather and climate disasters are increasing in frequency and severity, responsible for over 13,000 deaths, $1.75 trillion additional costs, and worsened morbidity over the last 40 years (3)(4)(5). In 2021, the Centre for Research on the Epidemiology of Disaster (CRED) recorded an increase in the annual number of recorded global disasters (432 disasters in 2021 vs. previous 20 year annual average of 357) (6).…”
Section: Introductionmentioning
confidence: 99%
“…7 Connecting these data to disaster events represents a logical application to understanding resulting morbidity and mortality, however, there exist only a handful of studies that have done so. [8][9][10][11][12] We conducted a self-controlled case series to address this gap and to determine the associations of hurricane events with hospitalizations for chronic conditions among older adults in the US. Specifically, we characterized admissions for chronic obstructive pulmonary disease (COPD), congestive heart failure (CHF), and diabetes among Medicare beneficiaries following several largescale hurricanes in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The overwhelming majority of older Americans have Medicare insurance, where analyses of Medicare data have been considered essential to informing healthcare, and to guide healthcare policy 7 . Connecting these data to disaster events represents a logical application to understanding resulting morbidity and mortality, however, there exist only a handful of studies that have done so 8–12 …”
Section: Introductionmentioning
confidence: 99%